PENGARUH MEKANISME CORPORATE GOVERNANCE DAN UKURAN KAP TERHADAP MANAJEMEN LABA - Mega Marsela; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2016)
The purpose of this study is to examine the impact of corporate governance mechanism to the earnings management (discretionary accruals) in the manufacturing companies. Corporate governance mechanisms in this study are institutional ownership, managerial ownership, independent board composition, independent audit committee composition, and audit firm size.The populations in this study are manufacturing companies which listed on BEI in the year 2012-2014. With the sampling method is purposive sampling. The method of selecting the data used in this research is purposive sampling method. This research was conducted by using documentation method which used data from annual report listed in Indonesia Stock Exchange (BEI) and the data from Indonesian Capital Market Directory (ICMD). The method of data analysis is used an OLS (Ordinary Least Square) regression. The total number of samples for this study is 219 companies. But, there are found 23 samples as outlier should be excluded from sample observation. So, the final samples for this study are 193 companiesThe results of this research showed that independent board composition, independent audit committee composition, managerial ownership and institutional ownership had negatively affected to the earnings management. Meanwhile, audit firm size had no significantly affected on earnings management. This result showed that corporate governance mechanism be able to reduce earnings management.